2001
DOI: 10.1002/gcc.1142
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in the SDHD gene in pedigrees with familial carotid body paraganglioma and sensorineural hearing loss

Abstract: Paraganglioma (PGL) is a rare disorder characterized by tumors of the head and neck region. Between 10% and 50% of cases of PGL are familial, and the disease is autosomal dominant and subject to age-dependent penetrance and imprinting. The paraganglioma gene (PGL1) has been mapped to 11q22.3-q23, and recently germline mutations in the SDHD gene have been identified. The SDHD region contains another gene, DPP2/TIMM8B, the homolog of which causes dystonia and deafness seen in Mohr-Tranebjaerg syndrome. Using fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
2
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 16 publications
1
55
2
1
Order By: Relevance
“…92 By mapping a mutation to chromosome 11 and referring to this region as paraganglioma locus 1 (PGL1), researchers discovered a genotype-phenotype discordance that was the result of genomic imprinting. 7,13 When PGL1 is transmitted through fathers, disease occurs in their offspring, whereas there is no disease phenotype when PGL1 is transmitted maternally. Genomic imprinting occurs when the maternally derived gene is inactivated during oogenesis, but because the gene is only reactivated during spermatogenesis, only males can pass the disease to their children.…”
Section: Inheritance Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…92 By mapping a mutation to chromosome 11 and referring to this region as paraganglioma locus 1 (PGL1), researchers discovered a genotype-phenotype discordance that was the result of genomic imprinting. 7,13 When PGL1 is transmitted through fathers, disease occurs in their offspring, whereas there is no disease phenotype when PGL1 is transmitted maternally. Genomic imprinting occurs when the maternally derived gene is inactivated during oogenesis, but because the gene is only reactivated during spermatogenesis, only males can pass the disease to their children.…”
Section: Inheritance Patternsmentioning
confidence: 99%
“…22,73 Furthermore, 86% of SDHD mutation-derived SHN-PGs are carotid body paragangliomas, presenting a unique and specific marker for predictive risk assessment. 7,22 Over half of the population with SDHD mutations is also at increased risk for the development of pheochromocytomas; therefore, individuals harboring SDHD mutations should undergo abdominal imaging to rule out adrenal masses. Since this was the first mutation to be linked to familial paragangliomas, extensive studies have now demonstrated that more genetically devastating mutations, such as splice site and nonsense mutations, result in earlier age of onset as well as an increased risk of developing multiple SHN-PGs and pheochromocytomas.…”
Section: Sdhdmentioning
confidence: 99%
“…However, CGH studies have shown losses of chromosome 11q in 22% of ileal and duodenal carcinoids, and this has involved the distal part of chromosome 11q, where the tumour suppressor gene SDHD is located (Kytola et al 2002). Germline mutations of SDHD have been reported in families with hereditary head and neck paragangliomas linked to 11q23, and in families with adrenal and extraadrenal phaeochromocytomas (Baysal et al 2000, Gimm et al 2000, Astuti et al 2001a,b, Badenhop et al 2001, Milunsky et al 2001, Taschner et al 2001. Two possible germline missense mutations (His50Arg and Gly12Ser) of the SDHD 446 www.endocrinology.org gene were reported in two sporadic midgut carcinoid tumours, which also had LOH at the SDHD locus on chromosome 11q23 (Kytola et al 2002).…”
Section: Midgut Nets (Carcinoids)mentioning
confidence: 99%
“…However, allelic expression analysis in fetal brain and lymphomatoid cell lines revealed biallelic expression (Malik et al, 2000). Recently, SDHD was shown to be monoallelically expressed in paragangliomas (Badenhop et al, 2001). If SDHD is also a monoallelically expressed tumor suppressor in other endocrine tissues, it is predisposed to gene inactivation through a single genetic 'hit' by loss of the expressed paternal allele, leading to a cell devoid of SDHD activity.…”
mentioning
confidence: 99%
“…First, there might be only a small allelic loss spanning neither of the two adjacent markers. Second, one allele might be inactivated by epigenetic mechanisms as methylation (Baysal et al, 1999(Baysal et al, , 2000 or third and most probably, one allele is the imprinted maternal allele (Badenhop et al, 2001).…”
mentioning
confidence: 99%